2012
DOI: 10.1111/j.1530-0277.2012.01953.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Alcohol Exposure and Attention‐Deficit/Hyperactivity Disorder on Psychopathology and Behavior

Abstract: Background The present study examined prevalence of psychiatric disorders and behavioral problems in children with and without prenatal alcohol exposure (AE) and attention-deficit/hyperactivity disorder (ADHD). Methods Primary caregivers of 344 children (8–16y, M=12.28) completed the Computerized Diagnostic Interview Schedule for Children-IV (C-DISC-4.0) and the Child Behavior Checklist (CBCL). Subjects comprised 4 groups: AE with ADHD (AE+, n=85) and without ADHD (AE−, n=52), and non-exposed with ADHD (ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 48 publications
4
44
1
Order By: Relevance
“…The largest difference in problem scores between PAE and control groups was observed in 2 studies in which children in the PAE group were selected based on high levels of PAE (>4 alcoholic drinks at least once per week, or ≥13 drinks per week throughout pregnancy). 26,34 Levels of PAE were not defined or reported in Brown et al 24 Pooled effects for the 3 summary problem scales showed no statistically significant differences between groups (P > .05; Fig 4). Age group comparisons were not possible.…”
Section: Cbcl (6-18 Y 2001)mentioning
confidence: 90%
See 2 more Smart Citations
“…The largest difference in problem scores between PAE and control groups was observed in 2 studies in which children in the PAE group were selected based on high levels of PAE (>4 alcoholic drinks at least once per week, or ≥13 drinks per week throughout pregnancy). 26,34 Levels of PAE were not defined or reported in Brown et al 24 Pooled effects for the 3 summary problem scales showed no statistically significant differences between groups (P > .05; Fig 4). Age group comparisons were not possible.…”
Section: Cbcl (6-18 Y 2001)mentioning
confidence: 90%
“…After screening and review, 23 articles were included in qualitative or quantitative analysis, with between 2 and 8 articles (total: 16) included in various meta-analyses. Tables 3 and 4 show the characteristics of included studies, according to presence of FASD (10 studies) [13][14][15][16][17][18][19][20][21] or PAE (14 studies), respectively [22][23][24][25][26][27][28][29][30][31][32][33][34] : one study reported data for both PAE and FASD. 35 Most were from North America (n = 15; 65.2%), followed by Australia (n = 4) and Canada (n = 2), with 1 study each from Finland and Taiwan.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviors associated with the effects of PAE appear similar to behaviors observed in children with attention deficit hyperactivity disorder (ADHD) [53][54][55][56]. However, there are differences between the two disorders [55,56].…”
Section: Fasd and Problematic Behaviormentioning
confidence: 86%
“…Of that number, 28 % met criteria for a mood or anxiety disorder, but the majority met criteria for externalizing disorders such as attention-deficit/hyperactivity disorder (ADHD), oppositional defiant disorder (ODD), or conduct disorder (CD). Moreover, recent findings from the same lab revealed that individuals with PAE were more likely to have a greater number of comorbid psychiatric illnesses than unexposed control subjects, and that the presence of a diagnosis of ADHD conferred the greatest degree of comorbid psychiatric risk [37].…”
Section: Middle Childhoodmentioning
confidence: 98%